2012
DOI: 10.1098/rsta.2012.0097
|View full text |Cite
|
Sign up to set email alerts
|

Binary recombination of para- and ortho-H 3 + with electrons at low temperatures

Abstract: Results of an experimental study of binary recombination of para-and ortho-H + 3 ions with electrons are presented. Near-infrared cavity-ring-down absorption spectroscopy was used to probe the lowest rotational states of H + 3 ions in the temperature range of 77-200 K in an H + 3 -dominated afterglow plasma. By changing the para/ortho abundance ratio, we were able to obtain the binary recombination rate coefficients for pure para-H + 3 and ortho-H + 3 . The results are in good agreement with previous theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
(79 reference statements)
2
19
0
Order By: Relevance
“…For the latter, Glosik's group has published papers that agree better with theoretical predictions [31,32]. However, the chemistry in their He-dominated plasmas is extremely complicated because of the long-lived metastable He, which keeps ionizing H 2 and producing H + 3 ; I find their analysis of ortho-to para-H + 3 conversion without taking this into account unsatisfactory.…”
Section: Dissociative Recombinationmentioning
confidence: 93%
“…For the latter, Glosik's group has published papers that agree better with theoretical predictions [31,32]. However, the chemistry in their He-dominated plasmas is extremely complicated because of the long-lived metastable He, which keeps ionizing H 2 and producing H + 3 ; I find their analysis of ortho-to para-H + 3 conversion without taking this into account unsatisfactory.…”
Section: Dissociative Recombinationmentioning
confidence: 93%
“…[14][15][16][17] and references therein. In studies of binary recombination of H + 3 ions in He/Ar/H 2 gas mixture it was observed that the decay of afterglow plasma is dependent on He number density [5,6,[18][19][20]. This indicates that a ternary He-assisted recombination process contributes to the overall recombination in afterglow plasma in He/Ar/H 2 gas mixture:…”
Section: Introductionmentioning
confidence: 97%
“…The advantage of the afterglow experiments is that H + 3 ions are rotationally thermalized by multiple collisions with ambient neutral gas molecules/atoms at properly chosen conditions [5,12]. In the recent afterglow type experiments the evolution of densities of H + 3 ions in the particular spin state and the thermalisation (rotational temperature within para and ortho nuclear spin manifolds and kinetic temperature) are monitored by a laser absorption spectroscopy (SA-CRDS -Stationary Afterglow with Cavity Ring-Down absorption Spectrometer [6,7,13]). One of the advantages of plasmatic environment is possibility to study ternary recombination processes assisted by neutrals, by electrons, or eventually by both of them, see Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterglows in helium-argon-hydrogen mixtures are the subject of the paper by Dohnal et al [22], presented at this meeting. The authors present evidence that para-H + 3 ions recombine much faster than ortho-H + 3 by both the binary and the three-body mechanisms.…”
Section: Afterglows In Rare-gas/h 2 Mixturesmentioning
confidence: 99%